The rhetoric of rape: a critical mapping of the discursive landscape in France = La rhétorique du viol: une recension critique du paysage discursif français - Evans, Dylan Sebastian (2013)
The Rhetoric of Rape: A Critical Mapping of the Discursive Landscape in France comprises three theoretically distinct, but thematically contiguous essays, each of which touches upon the highly contentious topic of 'la tournante'. From the expression 'faire tourner', meaning something like 'to hand, or to pass (something) around; to share', the word has taken on an additional, specialized, and more sinister sense: that of gang-rape. In place of the politically polarized lens through which 'la tournante' has been seen, The Rhetoric of Rape offers an alternative set of theoretical, respectively phenomenological (Maurice Merleau-Ponty), linguistic (John Langshaw Austin), and psychoanalytical (Sigmund Freud) perspectives from which the practice and its discursive conditions of possibility — its underlying archaeology — can be mapped. This triangulation of views reveals how certain political (pouvoir), epistemic (savoir), and erotic (plaisir) strategies mobilize rape and its rhetoric.